Lower-limb biomechanical asymmetry in maximal velocity sprint running - Exell, T.; Kerwin, D.; Irwin, G.; Gittoes, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Asymmetry analyses have provided valuable insight into submaximal running and walking gait. Knowledge of asymmetry in sprint running is limited due to traditional unilateral methods of data collection. The aims of the study were to develop asymmetry measures that included intra-limb variability and to investigate asymmetry of sprint running in an ecologically valid environment. Asymmetry was quantified for a group of sprint runners through the development of novel multifactorial asymmetry scores. The largest kinematic asymmetry values (7%) were smaller than the corresponding kinetic values (90%). The presence of significant athlete asymmetry suggested unilateral analyses may overlook important information. Information about individual athletes' asymmetry may also help to inform the coaching process.